The evaluation of competency certification program through the LSP P-1 at vocational high school - Budiyanto Budiyanto; Wardan Suyanto (Jurnal Pendidikan Vokasi, 2020)
This research aims to evaluate the competency certification program's implementation through the First-Party Professional Certification Institute (LSP P-1) at SMK N 2 Klaten.  The evaluation of the implementation of the competency certification program was reviewed on four aspects, e.g.: (1) context, (2) input, (3) process, and (4) product. This research is evaluation research based on the CIPP model (Context, Input, Process, Product). This research was conducted at SMK N 2 Klaten, which already had an LSP P-1license. The respondents were the principal, LSP chairman, secretary, treasurer, certification manager, chairman of the scheme committee, the competency test venue (TUK), and assessors. A questionnaire was used to collect data in this study. The data were analyzed with descriptive analysis. The result shows that: (1) the implementation of competency certification test through the LSP P-1 at State Vocational High School 2 Klaten in the context aspect is classified as very appropriate (83.93%), it is related to the policies and the goals of competency certification test; (2) in the input aspect is classified as very appropriate (88.82%), which meet the criteria of the assessor and the completeness of assessment tools; (3) in the process aspect is classified as very appropriate (88.59%), which leads to the suitability of the implementation procedures; and (4) in the product aspect is classified as very high (78.4%), for the achievement of competency certification test results and competency certificates.